2016
DOI: 10.1039/c6ob00168h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of boron-assisted oxime and hydrazone formations leads to the discovery of a fluorogenic variant

Abstract: We use kinetic data, photophysical properties, and mechanistic analyses to compare recently developed high-rate constant oxime and hydrazone formations. We show that when Schiff base formation between aldehydes and arylhydrazines is carried out with an appropriately positioned boron atom, then aromatic B-N heterocycles form irreversibly. These consist of an extended aromatic structure amenable to the tailoring of specific properties such as reaction rate and fluorescence. The reactions work best in neutral aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 28 publications
2
61
0
5
Order By: Relevance
“…Recently, we 1416 and others 1721 have demonstrated the thermodynamic and kinetic benefit of an ortho -boronic acid moiety in the formation of imines, as well as oximes and hydrazones. As thiazolidine formation potentially goes through an imine intermediate, we hypothesized that a boronic acid moiety installed at the ortho position of benzaldehyde would be able to activate the imine to facilitate thiazolidine formation (Figure 1b).…”
Section: Resultsmentioning
confidence: 98%
“…Recently, we 1416 and others 1721 have demonstrated the thermodynamic and kinetic benefit of an ortho -boronic acid moiety in the formation of imines, as well as oximes and hydrazones. As thiazolidine formation potentially goes through an imine intermediate, we hypothesized that a boronic acid moiety installed at the ortho position of benzaldehyde would be able to activate the imine to facilitate thiazolidine formation (Figure 1b).…”
Section: Resultsmentioning
confidence: 98%
“…126 Most notably, those BIQs proved to form irreversibly and thus they were found to be indefinitely stable in aqueous solution. This approach could be further developed into a fluorogenic reaction by using 2-hydrazinylphenol as a substrate, which results in the formation of highly emissive tetracyclic BIQ 108 .…”
Section: Stability Factorsmentioning
confidence: 99%
“…126 In this design, reactants are again rapidly trapped at the tetrahedral intermediate stage 162 / 163 , with the oxyanion coordinated to boron, and then more slowly rearrange to oximes 164 (Scheme 19). This strategy is an important new reaction for bioconjugation development.…”
Section: Discovery and Design Of Fast-reacting Substratesmentioning
confidence: 99%
“…11 Interestingly, the diazaborine product was found to survive boiling in solutions of either 10% HCl or 10% KOH. Recent and more detailed studies by the Bane 12 and Gillingham 13 groups revealed that the 2-FPBA-phenylhydrazine conjugation proceeds with rate constants over 10 3 M −1 s -1 . Despite the fast kinetics, this conjugation reaction remains less ideal for biological applications due to the poor stability and cytotoxicity of phenylhydrazine ( vide infra ), in addition to the high reactivity of 2-FPBA toward endogenous cysteines.…”
Section: Introductionmentioning
confidence: 99%